The Effect Of Using Several Types Of Mulch On The Growth And Production Of Watermelon Plants (Citrullus Vulgaris) - Likwi Yohanes Manengkey; Jemmy Najoan; Yefta Pamandungan (Sam Ratulangi University, 2022)
This study aims to determine the effect of several types of mulch on the growth and production of watermelon plants. This research has been carried out in Tuyat Village, Lolak District, Bolaang Mongondow Regency, North Sulawesi. This study was carried out for 3 months from February 2021 - April 2021. This study was compiled using a randomized block design (RAK) with 3 treatments, namely: A = Plastic mulch (black-silver), B = Straw mulch, C = No mulch. Each treatment was repeated 6 times so that there were 18 beds. To determine the effect of the treatment given, observations will be made every 1 week since the plant is 14 days after the plant (HST). Observations include Plant Length and Number of Leaves. Observations made after the plants produce or after harvest are fruit weight and fruit diameter. The results of this study indicate that there are differences between watermelon plants that use plastic mulch, and straw mulch and without using mulch on plant length, number of leaves, fruit weight, and fruit diameter of watermelon plants. The results of this study are expected to provide information to farmers about the effect of using the best mulch when cultivating watermelon plants. Keywords : Watermelon, Mulch, Plant Length, Number of Leaves, Fruit Weight and Fruit Diameter Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh beberapa jenis mulsa pada pertumbuhan dan produksi tanaman semangka. Penelitian Ini Telah Dilaksanakan Di Desa Tuyat Kecamatan Lolak Kabupaten Bolaang Mongondow, Sulawesi Utara. Penelitian Ini Dilaksanakan Selama 3 Bulan Sejak Bulan Februari 2021 sampai dengan April 2021. Penelitian Ini Disusun Menggunakan Rancangan Acak Kelompok (RAK) dengan 3 perlakuan yaitu : A = Mulsa plastik (hitam-perak), B = Mulsa jerami, C = Tanpa mulsa. Masing-masing perlakuan diulang sebanyak 6 ulangan sehingga terdapat 18 bedengan. Untuk mengetahui pengaruh dari perlakuan yang diberikan akan di lakukan pengamatan setiap 1 minggu sekali sejak tanaman berumur 14 hari setelah tanaman (hst). Pengamatan meliputi : Panjang Tanaman dan Jumlah Daun, Untuk Pengamatan yang dilakukan setelah tanaman berproduksi atau setelah panen adalah Berat buah dan Diameter buah. Hasil penilitian ini menunjukan adanya perbedaan antara tanaman semangka yang menggunakan mulsa plastik, mulsa jerami dan tanpa menggunakan mulsa terhadap panjang tanaman, jumlah daun, berat buah dan diameter buah tanaman semangka. Hasil penelitian ini diharapkan dapat memberikan informasi pada petani tentang pengaruh penggunaan mulsa yang terbaik pada saat membudidayakan tanaman semangka. Kata Kunci : Semangka, Mulsa, Panjang tanaman, Jumlah Daun, Berat Buah dan Diameter Buah